Individual cognitive stimulation in people with dementia: Good practices - Silva, R.; Santos-Costa, P.; Bobrowicz-Campos, E.; Gil, I.; Cardoso, D.; Apóstolo, J. (Gerontechnology V: Contributions to the Fifth International Workshop on Gerontechnology, IWoG 2022, 2023)
Background: Cognitive stimulation (CS) focuses on the intellectual and social stimulation of people with neurocognitive disorders (NCD or dementia). This intervention is widely disseminated in group settings and may not be accessible or adequate to all people with cognitive impairment. Making a Difference 3 (MD3) is an individual CS program in which family (informal) caregivers play the role of home care partners. These individual CS programs should be conducted based on key principles (good practices). Aim: To outline a set of good practices that should be adopted during the implementation of individual CS programs by caregivers. Methodology: Three main activities were conducted: i) Systematic review of the literature; ii) Translation and cultural adaptation of the MD3 to European Portuguese; iii) Randomized clinical trial with 52 dyads (caregiver and person with dementia) to assess the effectiveness of MD3 and its acceptability and applicability by older adults with dementia and their caregivers. Results: Thirteen good practices were outlined based on the values of respect, involvement, dignity, freedom of opinion and choice, understanding, tolerance, and cooperation with older adults with dementia. Conclusion: Several good practices were identified for the implementation of individual CS programs by caregivers of older adults with dementia. The healthcare professionals and experts in dementia care and the caregivers considered the recommended practices informative, inclusive, and valuable.